Alternative saline solutions to float foraminiferal tests - Semensatto, D. L.; Dias-Brito, D. (Cushman Foundation Foraminiferal Res, 2007)
Flotation has been widely used in studies of recent foraminifera in order to concentrate tests and save time during picking. In this paper, four flotation agents with different densities were compared: (1) trichloroethylene, TCE (C2HCl3), with a density of 1.46 g mL(-1); (2) sodium nitrate/sodium thiosulfate solution, SNT (NaNO3 + Na2O3S2 center dot 5H(2)O), with a density of 1.46 g mL(-1); (3) zinc chloride Solution, ZC (ZHCl(2)), with a density of 1.70 g mL(-1); and (4) sodium polytungstate solution, SPT (3Na(2)WO(4) center dot 9WO(3) center dot 5H(2)O), with a density of 2.50 g mL(-1). Comparison was carried out by means of qualitative and quantitative data. Results showed that ZC and SPT were the best flotation agents, recovering 91% and 96% of the total tests, respectively, whereas TCE and SNT recovered 59.1% and 72.8%, respectively. Both quantitative and qualitative results significantly improved with a higher density of the flotation liquid. Therefore, substitution of TCE with ZC or SPT solutions is strongly encouraged, because they are, additionally, less harmful to health and the environment. ZC is the most cost-effective, since its results were not significantly different from those of the SPT treatment. Carbon tetrachloride (CCl4) was not considered in this comparative study, because it has been banned in many countries and it is highly harmful to health and the environment.